2002
DOI: 10.1046/j.1439-0434.2002.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Fusarium moniliforme Isolated from Seeds of Different Host Species from Burkina Faso Based on Random Amplified Polymorphic DNA Analysis

Abstract: Random amplified polymorphic DNA (RAPD) analysis was used to assess genetic variation among 28 isolates of Fusarium moniliforme isolated from seed samples of six host species (rice, sorghum, maize, cotton, hibiscus and parkia) collected in Burkina Faso. Score‐able markers (128) were obtained with 20 random decamer primers. Cluster analysis with UPGMA using genetic distances showed that the isolates were of five main groups. In general, isolates from the same host species were found to group together in the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 12 publications
(12 reference statements)
0
9
0
3
Order By: Relevance
“…Bakanae is an important fungal disease of rice posing threat to rice production all over the world. The disease incidence of bakanae on rice has increased at an alarming rate taking its toll in diverse rice growing regions such as India, Japan, Taiwan, and Thailand ( Kini et al, 2002 ; Saremi, 2005 ; Bashyal and Aggarwal, 2013 ; Gupta et al, 2015 ; Bashyal et al, 2016a ; Fiyaz et al, 2016 ). Apart from causing significant yield losses ( Ou, 1985 ), the bakanae pathogen also affects seed quality ( Bashyal et al, 2014 , 2016b ; Fiyaz et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bakanae is an important fungal disease of rice posing threat to rice production all over the world. The disease incidence of bakanae on rice has increased at an alarming rate taking its toll in diverse rice growing regions such as India, Japan, Taiwan, and Thailand ( Kini et al, 2002 ; Saremi, 2005 ; Bashyal and Aggarwal, 2013 ; Gupta et al, 2015 ; Bashyal et al, 2016a ; Fiyaz et al, 2016 ). Apart from causing significant yield losses ( Ou, 1985 ), the bakanae pathogen also affects seed quality ( Bashyal et al, 2014 , 2016b ; Fiyaz et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is very limited information on occurrence and population structure of G. fujikuroi species complex associated with rice. Some data are available on the characterization of G. fujikuroi species complex populations associated with rice seeds from Nepal (Desjardins et al, 2000), few strains were reported associated with rice seeds from Burkina Faso (Kini et al, 2002) and with rice seedlings from Ghana (Amoah et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The random amplified polymorphic DNA (deoxyribonucleic acid) or RAPD technique is an alternative strategy for generating a polymorphic class of molecular markers (Williams et al, 1990), without any prior knowledge of DNA sequences in an organism. In Fusarium sp., RAPD has been applied in different approaches, such as to investigate the association between the genetic variability of the isolates and the locality of isolation and/or host plant populations (Kini et al 2002;Pamphile and Azevedo, 2002), to elucidate the taxonomic status and relationships among Fusarium isolates, races and species (Miedaner et al, 2001), to investigate pathogenicity variation (Nelson et al, 1997;Carter et al, 2002;Cramer et al, 2003). In addition, RAPD assay has been used to study the relationship between mycotoxin production in different fungal species and the RAPD profiles; however no conclusive data have been found to date (Jiménez et al, 2000;TranDinh et al, 1999).…”
Section: Introductionmentioning
confidence: 99%